Pengaruh Layanan Bimbingan Kelompok Terhadap Nomophobia Pada Siswa Kelas X SMA Negeri 1 Kualuh Leidong - Komariah, Siti; Nasution, Fauziah; I, Irwan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aimed to know the influence of group guidance service against nomophobia in students of class X students of high school. State I Kualuh Leidong Nomophobia is a disorder in which individuals feel uncomfortable, anxious, restless and followed by fear or worry when not operating a smartphone. Excessive use of smartphones can impact academic performance and increase anxiety levels affecting psychological aspects, interpersonal behavior, as well as social habits among adolescents. If this situation goes on non-stop, then the student’s personality will be affected and develop towards anti-social traits. Kelomopk tutoring services can help the socialization development of students and can address nomohobia behavior in students. The research methodology using quantitative approach, the population of the study was grade X students of Kualuh Leidong State I High School with a total of 26 students.. Sampling technique was conducted using random sampling technique established by the researcher. Data collection techniques by means of documentation, interviews and questionnaires. The data analysis/hypothesis testing tool uses the pre-experimental design (impure experiment) formula on SPSS processing. The results of the research conducted by the researcher obtained that the level of nomophobia in students has occurred decrease through increasing students’ knowledge and self-awareness towards nomophobia in students by using appropriate group tutoring services so this study suggests Ho was rejected and Ha was accepted by 0.00 value sig the influence of group tutoring services against nomophobia in students can be noted.